Dietary Magnesium Intake Affects the Vitamin D Effects on HOMA-β and Risk of Pancreatic β-Cell Dysfunction: A Cross-Sectional Study - Gong, Rongpeng; Liu, Yuanyuan; Luo, Gang; Yang, Lixin (Frontiers in Nutrition, 2022)
Background Some studies have shown that, the circulating vitamin D (Vit D) concentration in the body exerts a crucial role in regulating the pancreatic β-cell function. Meanwhile, the role of magnesium is important in the synthesis of Vit D, since it is an essential element for activating Vit D. Nevertheless, there remains insufficient studies concerning whether dietary Magnesium intake influences the association between Vit D and risk of pancreatic β-cell dysfunction. Hence, this cross-sectional study aimed to assess the effect of Magnesium intake alterations on the association between serum Vit D levels and the risk of pancreatic β-cell dysfunction. Methods This large-scale cross-sectional study involves four cycles of National Health and Nutrition Examination Survey (NHANES) (2007–2014), with totally 4,878 participants. Groups were divided depending on the median daily intake of Magnesium, namely, the low intake group (Magnesium intake <267 Magnesium/d) and the high intake group (Magnesium intake ≥ 267 Magnesium/d). By constructing multiple multivariate linear and logistics regression models, the associations between serum Vit D levels and HOMA-β, as well as between serum Vit D levels and the risk of pancreatic β-cell dysfunction were explored at different Magnesium intakes. Results In this cross-sectional study, the serum Vit D level is independently correlated with the HOMA-β index [β: 0.65 (0.40–0.90)] and the risk of pancreatic β-cell dysfunction [OR: 0.95 (0.92–0.98)]. Moreover, such correlations are affected by different dietary Magnesium intakes (P for interaction < 0.001). Conclusion According to the results of this study, the dietary Magnesium intake influences the associations of serum Vit D levels with HOMA-β index and pancreatic β-cell dysfunction. Besides, the finding requires validation through more RCT or cohort studies.